Integrated care improves risk-factor modification after stroke: Initial results of the integrated care for the reduction of secondary stroke model - Joubert, J.; Reid, Christopher; Barton, D.; Cumming, T.; McLean, A.; Joubert, L.; Barlow, J.; Ames, D.; Davis, S. (2009)
Objective: Despite evidence demonstrating that risk- factor management is effective in reducing recurrent cerebrovascular disease, there are very few structured care programmes for stroke survivors. The aim was to implement and evaluate an integrated care programme in stroke.Methods: 186 patients with stroke were randomised to either the treatment (integrated care) or control (usualcare) group and were followed up over 12 months. The Integrated Care for the Reduction of Secondary Stroke (ICARUSS) model of integrated care involved collaboration between a specialist stroke service, a hospital coordinator and a patient's general practitioner. The primary aim was to promote the management of vascular risk factors through ongoing patient contact and education.Results: In the 12 months poststroke, systolic blood pressure (sBP) decreased in the treatment group but increased in controls. The group difference was significant, and remained so when age, sex, disability and sBP at discharge were accounted for (p = 0.04). Treatment patients also exhibited better modification of body mass index (p = 0.007) and number of walks taken (p<0.001) than controls. Rankin scores indicated significantly reduced disability in treatment patients relative to controls in the year poststroke (p = 0.003). Conclusions: Through an integrated system of education, advice and support to both patient and GP, the ICARUSS model was effective in modifying a variety of vascular risk factors and therefore should decrease the likelihood or recurrent stroke or vascular event.